A prática como componente curricular: formação inicial e constituição da identidade docente nos Cursos de Licenciatura em Geografia - UFU e UFTM - Gomes, Viviane Caetano Ferreira (2020)
Recently a serie of measures and actions were taken to establish reforms and guide the teachers training politics in Brasil. Between those, it stands out, after the 2000‟s, the National Curricular Guidelines presenting the need of rupture with the model 3+1, that during the years characterize the teachers training in the country. One of the measures introduced was the curricular restructuring of the gradiation curses, with the main objective of overcoming the dichotomy between theory and practice and, therefore, the dialogue between specific subjects and pedagogical subjects, institutionalizing, in this context, Practice as a Curricular Component. (PCC). Given this, the research problem is based on the obstacles surrounding the interlocution between the academic and school dimension of geographic knowledge, verified in the scenario of Geography teacher training in Brazil. For this purpose it was elected as the main point of discussion, the PCC, its readings, dynamics, limits and possibilities, departing from the reality of the Undergraduate Geography Courses in Universidade Federal de Uberlândia (UFU) and Universidade Federal do Triângulo Mineiro (UFTM). The study had as its general objective the evaluation of Practice as a Curricular Component, its relationship with the Supervised Internship and its reflexes in the theoretical and professional field throughout the initial teaching formation in Geography. The specific objectives of the work include: (i) to understand the institutionalization of Practice as a Curricular Component within the scope of curricular policies for teacher training in Brazil; (ii) make explicit the contributions of Practice as a Curricular Component in the relationship between knowledge, practices and the constitution of the identity of teachers(s) in Geography; (iii) to evaluate the Practice as a Curricular Component from the Pedagogical Projects of the evaluated Courses and teaching plans; (iv) to analyze the practice, from interviews and reports on the trajectories of formation and teaching work in Geography. Methodologically, the study was based on the concepts of Qualitative Research when evaluating Pedagogical Projects and teaching plans in relation to the PCC and during data collection, based on semi-structured interviews and the application of scripts for writing reports. In total, three Pedagogical Projects were evaluated, one referring to the Degree in Geography (UFU), corresponding to the period from 2006 to 2018, and two, referring to the Degree in Geography (UFTM), associated with the transition period between the Pedagogical Project (2010-2014) and the Pedagogical Project established in 2014. In relation to teaching plans, a total of fifty plans of these were evaluated, seventeen referring to PIPE-UFU and thirty-three referring to APC-UFTM. The interviews involved ten teacher and written reports of twenty-six students, total of subjects belonging to the two courses evaluated. From a structural point of view, the work was organized into five sections: I) Teacher professional training in Brazil: curricular policies and the institutionalization of Practice as a Curricular Component; II) Practice as a Curricular Component: from knowledge and practices to teaching identity in Geography; III) Practice as a Curricular Component in UFU and UFTM Geography Degree Courses; IV) Routes of Practice: conceptions and formative experiences in the teaching constitution in Geography; V) Routes of Practice: trajectories and formative experiences of undergraduate students. As a result, the study points out that, despite of different arrangements in relation to the PCC, in both courses there is a fragmentation of the training process as, both internally and interdisciplinarily, they face difficulties in terms of interlocution between the academic and school dimensions of geographical knowledge. The treatment of PCC, in the two courses in question, reveals that the Degree still succeeds in constituting a collective project to involve, even at different levels and approaches, all disciplines and formative stages.